Pemanfaatan Minyak Jelantah dengan Ampas Tebu Teraktivasi sebagai Katalis Sekaligus Media Adsorpsi untuk Produksi Biodiesel Mendukung Indonesia Emas 2045 - Faldanil Mawan Zhuhri; Raka Afifuddin Abrar; Agus Widayoko; Nurul Hidayati (SMA Trensains Muhammadiyah Sragen, 2026)
The increasing use of diesel fuel in Indonesia has prompted the need for more environmentally friendly alternative energy sources, one of which is through the use of used cooking oil as a raw material for biodiesel. This study aims to determine the effectiveness of activated bagasse as a catalyst and adsorbent in improving biodiesel quality. The method used is a laboratory experiment that includes the process of purifying used cooking oil with RBD adsorption, transesterification reaction using activated bagasse catalyst, and testing biodiesel quality through ALB, density, flash point, and yield parameters. The results showed that activated bagasse was able to reduce the free fatty acid content from 0.20224% to 0.04096% after purification, and in biodiesel it decreased further to 0.0256%. The transesterification process took 65 minutes, close to the standard 60 minutes, with the resulting biodiesel having a density of 0.86 g/mL, a flash point of 98°C, and a yield of 74%. Based on these results, activated sugarcane bagasse is considered quite effective as an environmentally friendly catalyst in the production of biodiesel from waste cooking oil and has the potential to be a more beneficial solution for the utilization of biomass waste.